Gambaran Kekerasan Dalam Novel Jane Eyre Karya Charlotte Bronte - Abror, Amani (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
The research aims to describe the depiction of violence that occurs in the novel Jane Eyre by Charlotte Bronte. The method used in this study is qualitative descriptive with an objective approach. The theory of violence used in this study is Robert F. Litke's theory, with the dimensions of personal and institutional violence in the form of physical and the dimensions of personal and institutional violence in the form of psychology. The results of the study explain that the description of violence contained in Jane Eyre's novel in this study is (1) personal violence in the form of physical, behavior that causes pain or injury and death. (2) Personal violence of a psychological nature, such as those committed by Mrs. Reed, Mr. Blackhurst, Rochester, Celine and Bertha Mason, crimes committed by the father and sister of Rochester and the Masons against Rochester. Non-physical/psychological violence is carried out by means of character assassination and swearing. (3) Institutional violence with physical violence, occurs in school institutions by providing inappropriate feeding to students at Lowood schools. (4) Institutional violence in the form of psychological, the occurrence of a business marriage carried out by two families of Mr. Rochester and the Mason family which has an impact on the lives of Mr. Rochester and Bertha Mason.